Skin Reactions Developing After Anti-Tumor Necrosis Factor Treatment: A Paradoxical Side Effect - Öznur KUTLUK; Ayşe ÜNAL ENGİNAR and Nilüfer BALCI and Bülent BÜTÜN and Cahit KAÇAR (Archives of Rheumatology, 2019)
The use of anti-tumor necrosis factor (anti-TNF) therapies for treatment of rheumatic diseases is increasing every day and the results are positive. Case reports about skin reactions developing after use of these medications - newly developing psoriasis, increase/flare-up of existing psoriasis - are found in the literature at rates that cannot be ignored. Psoriasis developing after the use of these agents for treatment is a paradoxical side effect, with no clear understanding of the cause though several hypotheses exist. In this article, we present five cases with this paradoxical side effect developing after anti-TNF treatment accompanied by the literature with the aim of aiding in finding an approach to these cases.